Honesty and inquiry: W.K. Clifford's ethics of belief. Issue 4 (3rd July 2020) - Nottelmann, Nikolaj; Fessenbecker, Patrick
ABSTRACT: W.K. Clifford is widely known for his emphatic motto that it is wrong, always everywhere, and for anyone, to believe anything upon insufficient evidence. In fact, that dictum and Clifford's condemnation of a scheming self-deceptive shipowner sum up how his ethics of belief is most often remembered and how it has been subsequently interpreted. In contrast to other recent interpretations, we argue that the motto is misleading as a guide to Clifford's position. It is best understood as essentially a rhetorical flourish. Moreover, in important ways the scheming shipowner is not stereotypical of the kind of believer Clifford thought blameworthy. A careful study of Clifford's various writings on the ethics of belief finally reveals him not to be an evidentialist in the Humean tradition. Rather, inspired by Charles Darwin's work in moral psychology, he applied an evolutionary-functional virtue ethics to the doxastic realm. This perspective allows a fruitful examination of his engagement with contemporaries like Matthew Arnold. It also allows us to recognize him as a predecessor to modern attributionist accounts of blameworthy belief.